Students' Difficulties In Reading Short Stories In Junior High School Wawonii Tenggara - Roy, Aiswarya; Tohamba, Citra Prasiska Puspita; Muflihun, Muflihun; Almuthmainnah, Almuthmainnah (LETS: Journal of Linguistics and English Teaching Studies, 2024)
This study aims to investigate students' difficulties in reading short stories at Junior High School Wawonii Tenggara. This study was conducted in grade 8 of Junior High School Wawonii, with a sample of 5 students selected purposively. This research has conducted last for one week, namely May 15-18, 2023. To achieve thisgoal, the researcher used a qualitative design and the semi-structured interview methods to collect data. To analyze the data, the researcher used data condensation techniques, data display, and drawing conclusions. The results of this study indicate that there were three students' difficulties in reading short stories: difficulty in understanding a word or piece of vocabulary, difficulty in understanding long sentences, difficulty on understanding main ideas, and each student has his/her own efforts to solve the problems faced when reading short stories.